2022
DOI: 10.1002/acm2.13782
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐planning approaches to intensity modulated proton therapy and the impact on dose‐weighted linear energy transfer

Abstract: Purpose We quantified the effect of various forward‐based treatment‐planning strategies in proton therapy on dose‐weighted linear energy transfer (LETd). By maintaining the dosimetric quality at a clinically acceptable level, we aimed to evaluate the differences in LETd among various treatment‐planning approaches and their practicality in minimizing biologic uncertainties associated with LETd. Method Eight treatment‐planning strategies that are achievable in commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In addition, a structure called "CTV-GTV" is created as the CTV with the GTV subtracted, for each of the cases. Two parallel opposed beams from 90 • and 270 • are used, as recommended by Faught et al 15 We also performed experiments (not shown) with 4, 8, and 16 beams with similar results for the effect on LET d . An ROI called "Entrance" for gauging the entrance dose is created as a 2 cm long cylinder with radius 0.5 cm aligned with the beam central axis 1 cm from the patient surface to the left.…”
Section: Phantom Casementioning
confidence: 74%
See 2 more Smart Citations
“…In addition, a structure called "CTV-GTV" is created as the CTV with the GTV subtracted, for each of the cases. Two parallel opposed beams from 90 • and 270 • are used, as recommended by Faught et al 15 We also performed experiments (not shown) with 4, 8, and 16 beams with similar results for the effect on LET d . An ROI called "Entrance" for gauging the entrance dose is created as a 2 cm long cylinder with radius 0.5 cm aligned with the beam central axis 1 cm from the patient surface to the left.…”
Section: Phantom Casementioning
confidence: 74%
“…Faught et al 15 studied the effects on LET d for various treatment planning approaches for IMPT under uncertainty. Using dose-based planning, without any LET d -based functions included in the optimization, they observed that when the magnitude of the range uncertainty included in the optimization was increased, the LET d in the target decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating LET changes with beam arrangement have shown that LET max (Appendix B) increases significantly as the angle between the two beams approaches 0 • due to a build-up of high LET in a small region [10,63,64]. Faught et al [10] observed an LET max increase of 3.3 keV/µm immediately outside the target boundary when a beam angle of 60 • is used compared to 180 • , while inside the target LET max increased by 1.2 keV/µm and LET mean (Appendix B) remained unchanged. Fjaera et al [64] made similar observations in that narrowing the angle between two lateral beams increased LET within the brainstem; however, with the addition of a third vertex beam, LET mean decreased.…”
Section: Beam Field Configuration and Spot Sizementioning
confidence: 99%
“…A universal RBE of 1.1 is currently adopted in a clinical setting [4,5], despite increasing to values in excess of 2 [6] in the distal Bragg Peak region. Clinically, the distribution of RBE for a treatment plan is complicated further by the use of the spreadout Bragg Peak (SOBP), due to the higher degree of modulation compared to a pristine Bragg Peak (e.g., IMPT) [7][8][9][10]. By disregarding RBE exceeding 1.1 in the distal region, we underestimate the biological effect inside critical structures, potentially having a negative effect on treatment outcomes [11].…”
Section: Introductionmentioning
confidence: 99%